Teaching and learning with virtual teams - Ferris, Sharmila Pixy; Godar, Susan Hayes 1948- (Gale virtual reference library, 2006)
"This book investigates issues around teams in the virtual and hybrid classroom, offering a view of current research and practice on the subject of virtual and collaborative teams in teaching and learning"--Provided by publisher.